Preference index supported by motivation tests in Nile tilapia - Maia, Caroline Marques; Volpato, Gilson Luiz (Public Library of Science (PLoS), 2017)
The identification of animal preferences is assumed to provide better rearing environments for the animals in question. Preference tests focus on the frequency of approaches or the time an animal spends in proximity to each item of the investigated resource during a multiple-choice trial. Recently, a preference index (PI) was proposed to differentiate animal preferences from momentary responses (Sci Rep, 2016, 6:28328, DOI: 10.1038/srep28328). This index also quantifies the degree of preference for each item. Each choice response is also weighted, with the most recent responses weighted more heavily, but the index includes the entire bank of tests, and thus represents a history-based approach. In this study, we compared this PI to motivation tests, which consider how much effort is expended to access a resource. We performed choice tests over 7 consecutive days for 34 Nile tilapia fish that presented with different colored compartments in each test. We first detected the preferred and non-preferred colors of each fish using the PI and then tested their motivation to reach these compartments. We found that fish preferences varied individually, but the results were consistent with the motivation profiles, as individual fish were more motivated (the number of touches made on transparent, hinged doors that prevented access to the resource) to access their preferred items. On average, most of the 34 fish avoided the color yellow and showed less motivation to reach yellow and red colors. The fish also exhibited greater motivation to access blue and green colors (the most preferred colors). These results corroborate the PI as a reliable tool for the identification of animal preferences. We recommend this index to animal keepers and researchers to identify an animal's preferred conditions.